UNDERSTANDING FARAID KNOWLEDGE BASED ON LITERATURE - Azuan, Nur Madihah; Jalil, Mohammad Syukri (Jurnal ’Ulwan, 2024)
Islam is a lifestyle. It’s a religion that accepts all facets of a person’s life. Muslims can benefit from the laws and values that Allah has established in Islam both here on earth and in the afterlife. Islam as a result established the faraid, a just system for allocating property to heirs who are legitimate. To guarantee that each family member receives an equal portion of the legacy property, this is crucial. The fundamental problem that motivated this study provides a workable solution that will increase public awareness of and knowledge about faraid and lay the groundwork for further investigation. The literature and library studies serve as the foundation for the research process. The research’s conclusions demonstrate the degree of awareness and comprehension among Muslims. There are evident problems with the division and counting of each component, though. Therefore, it is important to urge the Muslim community to become more knowledgeable about faraid and to strengthen the government’s capacity in order to prevent the issue of unclaimed property.